EXAMINING THE RELATIONSHIP BETWEEN PUBLIC SPENDING ON EDUCATION AND UNEMPLOYMENT PROBLEM IN NIGERIA - Binuomoyo , Olayinka K. (Malaysian Journal of Business and Economics (MJBE), 2020)
Much of the problems of unemployment in the past have been placed on the inadequacy of the country’s schooling system to be able to impact needed skills. Empirical and theoretical evidence is overwhelmingly in support of the significant role of public expenditure in education having a multiplier effect on employment. Empirical evidence shows that this is not consistent in a macroeconomic framework. Government has been indicted for not doing enough to support education with its budgetary shortcomings to the sector. This study investigates the impact of government spending on unemployment in Nigeria. OLS estimates adopted for secondary data regressed over the 27 years for unemployment, federal government recurrent expenditure on education and economic growth indicated that while growth is significant and indeed influence unemployment negatively in line with our a-priori expectation, it is not the same for the impact of public expenditure on education. Our findings from this were that while Nigeria’s educational capacity has increased, its impact is shallow as the economy is unable to absorb the graduates. To address this anomaly, the government will need to enhance its effectiveness through creating adequate channels for enterprise growth and sustainability which will increase the latter’s capacity to employ more labour.